Effect of diffusion on composite material properties - Yeoh, Wu Lieh (2014)
The need for a material with better enhancement has always been there ever since the advances of technology in the marine-time applications. In the past, most of the materials that were used in marine-time applications were super-alloys. Steel is the most commonly used material as it is known for its strength. As of now, deep oil harnessing is much deeper as compare to the past and this pushed the limit of steel to its limit. As the deepness for harnessing increases, the anchors can no longer undergo the natural weight of the pipeline and it result in additional loading within the structure. Thus, this will lead to a burst in pipeline as seen from majority of the oil-spills. Therefore, there is a high demand for new materials to substitute steel with a lighter weight and at the same time providing a stronger mechanical strength. This material is the fiber reinforced composite.